1988
DOI: 10.1055/s-0038-1647055
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Increases Fibrin Clot Lysis by Neutralization of Plasminogen Activator Inhibitor No Evidence for a Cofactor Role of Protein S

Abstract: summaryThe effect of purified human activated protein G (APC) on fibrinolysis was studied using a clot iysis system consisting of purified glu-plasminogen, tissue-type plasminogen activator, plasminogen activator inhibitor (released from endothelial cells or blood platelets), fibrinogen, 125T-fibrinogen and thrombin. All proteins were of human origin.In this system APC could increase fibrinolysis in a dose dependent way, without affecting fibrin formation or fibrin crosslinking. However, this profibrinolytic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 18 publications
2
25
0
1
Order By: Relevance
“…This same value was obtained if PAI-1 inhibition of APC was monitored in the presence of 220 nM protein S and 0 -50 M PC/PS or PC/PS/PE vesicles (data not shown). These results are consistent with other data in the literature (8). Therefore, unlike the potent profibrinolytic effect observed for APC in vivo (4), in whole blood clot lysis assays (6), and in endothelial cell culture supernatants (5), kinetic data in the purified system suggest that human APC neutralization of PAI-1 by itself may not significantly contribute to up-regulation of the fibrinolytic cascade.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This same value was obtained if PAI-1 inhibition of APC was monitored in the presence of 220 nM protein S and 0 -50 M PC/PS or PC/PS/PE vesicles (data not shown). These results are consistent with other data in the literature (8). Therefore, unlike the potent profibrinolytic effect observed for APC in vivo (4), in whole blood clot lysis assays (6), and in endothelial cell culture supernatants (5), kinetic data in the purified system suggest that human APC neutralization of PAI-1 by itself may not significantly contribute to up-regulation of the fibrinolytic cascade.…”
Section: Resultssupporting
confidence: 82%
“…This is probably due to the fact that prolonged incubation of human APC with high concentrations of PAI-1 results in a minimal decline in the activity of the proteinase. In support of this, results of an in vitro clot lysis assay using purified components of the APC anticoagulant pathway have disputed whether this mechanism can contribute to the profibrinolytic property of human APC in vivo (8). Such results have raised the possibility that other factor(s) in blood may be involved in APC up-regulation of the fibrinolytic cascade (8).…”
Section: Activated Protein C (Apc)mentioning
confidence: 92%
See 1 more Smart Citation
“…The relative amounts of plasminogen activators and APC at sites of hemostasis and thrombosis are not known and likely exhibit both spatial and temporal variability due to differing rates of synthesis, metabolism, and adsorption to surfaces. We found no accelerating effect on protein S, phospholipid, and CaClz on the inactivation of PA1 by APC in a purified, reconstituted system, results similar to those reported by de Fouw et al (1988). However, de Fouw et al (1986 have observed protein S to enhance the acceleration of whole human blood clot lysis by APC in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…* rnent (UK). p < 0.05 vs. before urokinase treatpotentiating the activity of plasminogen acti vators [6,7], which is independent of protein S [10], Recent reports suggested the efficacy of protein C as an extrinsic antithrombotic agent [ l l-l 3] or as an agent to prevent reste nosis after percutaneous transluminal coro nary angioplasty [ 14],…”
Section: Discussionmentioning
confidence: 99%